Peran SMA Terbuka Dalam Memenuhi Kewajiban Belajar Di Kecamatan Cianjur - Sulis Tyaningsih; Siti Qomariyah (International Forum of Researchers and Lecturers, 2024)
Open High School is a subsystem of education at the secondary education level that prioritizes independent learning activities of students with limited guidance from others. Open High School is one of the alternative education service models at the secondary level and is not a new institution or UPT that stands on its own, but is based on an existing regular high school. This research aims to describe the concept of Open High School and its role in fulfilling learning obligations. The research method used is descriptive qualitative research method. The qualitative research method according to Sugiyono is a research method based on the philosophy used to research on scientific conditions (experiments) where the researcher is an instrument, while qualitative data collection and analysis techniques emphasize meaning. The results showed that the Open High School in Cianjur Subdistrict is a school attached to Pasundan 2 Cianjur High School, the curriculum used is not much different from the curriculum used in the Parent High School, only the learning process is different. Open High School has a very important role in fulfilling learning obligations for those who are constrained or have limitations to attend regular education.